2013
DOI: 10.1590/s0080-623420130000600003
|View full text |Cite
|
Sign up to set email alerts
|

A manipulacao de prematuros em uma Unidade de Terapia Intensiva Neonatal

Abstract: RESUMOOs prematuros são submetidos a diversas manipulações e procedimentos durante internação em unidades neonatais, com consequências deletérias para a saúde. O objetivo do presente estudo foi descrever a manipulação a que são submetidos os prematuros durante as 24 horas em uma unidade de terapia intensiva neonatal (UTIN). Estudo observacional, descritivo, exploratório, realizado com 20 prematuros, filmados continuamente por um período de 24 horas, de setembro de 2008 a março de 2009 numa UTIN. Os prematuros … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 13 publications
0
11
0
19
Order By: Relevance
“…(14) In addition, other factors related to health professionals' practices influence the occurrence of bloodstream infections associated with the catheter. These factors involve the manipulation of the catheter and its connections, contamination of the intravenous solutions to be infused, and colonization of the catheter due to the migration of microorganisms on the skin around the catheter insertion site to inside the body.…”
Section: Discussionmentioning
confidence: 99%
“…(14) In addition, other factors related to health professionals' practices influence the occurrence of bloodstream infections associated with the catheter. These factors involve the manipulation of the catheter and its connections, contamination of the intravenous solutions to be infused, and colonization of the catheter due to the migration of microorganisms on the skin around the catheter insertion site to inside the body.…”
Section: Discussionmentioning
confidence: 99%
“…The preterm infant’s trajectory starts with the hospitalization, often over long periods, at neonatal services, where they are exposed to many stimuli related to lighting, noise and manipulation 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Infants admitted to an NICU over three months underwent 3,283 invasive procedures, the most frequent being calcaneal puncture for blood collection, endotracheal aspiration and intravenous insertion of the cannula (Barker & Rutter, 1995). Furthermore, considering the total number of manipulations that infants usually undergo in the NICU, a total of 768 manipulations and 1,341 procedures were performed, with each manipulation having a mean of 2.2 multiple procedures (Pereira et al, 2013 According to the International Association for the Study of Pain (IASP), pain is defi ned as: "an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage" (1994/2017, IASP Taxonomy para.3). The systematic review of Valeri, Holsti, and Linhares (2015) showed that the larger number of stressful and painful procedures in the neonatal period was associated with several future impacts, such as growth delay after birth and motor and cognitive development impairment.…”
Section: Contacto "Piel a Piel" En La Prevención Del Dolor En Bebés Pmentioning
confidence: 99%